Marketing Strategies in Micro Cake Business to Increase Competitiveness (Case Study on Micro Business Hii.Misu in Serang District, Serang City) - Ayu Shofiyah; Gugun Gunawan; Cristiana Adjar Astuti (Dinasti Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in driving Indonesia's economic growth, particularly through their capacity to enhance the economic landscape of local communities. This study aims to determine marketing strategies in micro cake business to increase competitiveness in Serang City. The research adopts a qualitative methodology, utilizing purposive sampling to select a total of ten respondents, which includes one business owner, two employees, and seven consumers. Data analysis is conducted using several strategic tools, including the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, as well as the Internal-External (IE) matrix, SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM) analysis. The findings reveal that the weighted average score for the IFE is 2.85, while the average score for the EFE is 3.27. These scores are instrumental in determining the business's position within the IE matrix, indicating its growth and build. A subsequent SWOT analysis identifies and examines strategies based on the business's strengths, weaknesses, opportunities, and threats. The strategies derived from the SWOT analysis are then prioritized using the QSPM analysis, revealing that the foremost priority strategy for UMKM Hii.Misu is market development, which has the highest Total Attractiveness Score (TAS) of 5.692. This strategy enables UMKM to expand its reach to external markets by leveraging social media marketing to promote its authentic products.